Unfolding the Mysteries of Cell-based Human Leukocyte Antigen Crossmatching in Solid Organ Transplantation - Shruti Tapiawala; Suchita Jogale; Dolly Danielle; Anil Handoo (Indian Journal of Transplantation)
Since 1960s when transplantation was initiated in the world, pre formed HLA antibodies in the recipient’s serum against the donor have been associated with immediate allograft loss, inferior early and late graft outcomes. The immune system’s recognition of foreign HLA antigens can trigger an immune response leading to graft rejection1. The necessity to identify those at risk of allograft loss and improving short term and long-term outcomes led to the development of crossmatch procedures. This test plays a crucial role in preventing transplant rejection by detecting pre-existing antibodies in the recipient that target donor HLA molecules. This article provides an overview of cell based crossmatches such as Complement Dependent cytotoxicity crossmatch (CDCXM) and Flow cytometry crossmatch (FCXM). The techniques, methodologies, advantages, limitations and application in day-to-day practice are discussed. The article will be helpful to both clinicians and laboratory personnel dealing with organ transplantation.